Urinary Tract Infections and Inadequate Insulin Therapy as a Precipitating for Diabetic Ketoacidosis in Type 1 Diabetes Mellitus: A Case Report - Anak Agung Ayu Mita Astari; Dewi Catur Wulandari (PT BMW Journal Sejahtera, 2024)
Background: Diabetic ketoacidosis (DKA) is a severe acute metabolic complication associated with diabetes mellitus. It is particularly prevalent in patients with Type 1 diabetes, where inadequate insulin therapy can lead to significant morbidity and mortality. Case: We present the case of an 18-year-old girl diagnosed with Type 1 diabetes mellitus. She arrived at the hospital exhibiting shortness of breath and was found to have a C-peptide level of 0.33, which, alongside her history of irregular insulin injections, indicated poor adherence to insulin therapy. Upon physical examination, the patient appeared lethargic, had apathetic consciousness, a tachycardic heart rate of 127 beats per minute, and an elevated axillary temperature of 37.8°C. Notably, Kussmaul breathing was also observed. Results: Laboratory findings revealed elevated white blood cell count (15,950/μL), hyperglycemia (blood sugar level of 379 mg/dL), and severe metabolic acidosis, as indicated by arterial blood gas analysis (pH 6.89, HCO3 1 mmol/L). Urinalysis demonstrated the presence of albumin (+1), glucose (+2), ketones (+3), leukocytes (+3), and bacteria. The patient required intensive care monitoring for five days before being transitioned to the general ward for an additional three days of treatment. Conclusion: DKA is characterized by hyperglycemia, hyperketonemia, and metabolic acidosis, all of which are indicative of insufficient insulin therapy in patients with Type 1 diabetes. This case highlights the critical importance of adherence to insulin therapy for achieving optimal glycemic control. Effective management and discipline in treatment are essential to prevent DKA and reduce its associated mortality.